1997
DOI: 10.1016/s0304-3959(97)03339-3
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous field stimulation (CFS): a new powerful method to combat itch

Abstract: Scratching the skin, while instantly relieving itch, often aggravates itch over time due to skin injury. To relieve itch, without damaging the skin, a new technique termed cutaneous field stimulation (CFS) was developed and tested on 21 subjects. CFS uses a flexible plate with needle-like electrodes (n = 16) to electrically stimulate nerve fibres in the superficial skin. The electrodes were stimulated consecutively (4 Hz per electrode, pulse duration 1 ms, intensity 0.4-0.8 mA, 25 min). CFS resulted in a prick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 26 publications
6
96
1
6
Order By: Relevance
“…Experimental itch and accompanying dysesthesiae were enhanced by a local anesthetic ) and attenuated in hyperalgesic skin surrounding a capsaicin injection ). These studies demonstrated functional interactions between pruritic and nociceptive neural systems and lend support to the hypothesis that the mechanisms subserving itch are inhibited centrally by mechanisms that underlie pain and hyperalgesia Brull et al 1999;Graham et al 1951;Nilsson et al 1997;Ward et al 1996).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Experimental itch and accompanying dysesthesiae were enhanced by a local anesthetic ) and attenuated in hyperalgesic skin surrounding a capsaicin injection ). These studies demonstrated functional interactions between pruritic and nociceptive neural systems and lend support to the hypothesis that the mechanisms subserving itch are inhibited centrally by mechanisms that underlie pain and hyperalgesia Brull et al 1999;Graham et al 1951;Nilsson et al 1997;Ward et al 1996).…”
Section: Introductionsupporting
confidence: 60%
“…Another property expected of a candidate pruriceptive neuron in the CNS is that its activity is inhibited by algesic stimuli applied to normal skin and by the development of algogenic dysesthetic states such as allodynia and hyperalgesia (Bickford 1938;Brull et al 1999;Graham et al 1951;Koppert et al 1993;Nilsson et al 1997;Ward et al 1996). Rather than being inhibited by capsaicin, most of the STT neurons in the present study were vigorously excited, after which they became sensitized to stroking and to punctate stimuli.…”
Section: Neuronal Response Properties That Might Contribute To Itch Amentioning
confidence: 53%
“…We noticed in previous studies that IES actually activates C fibers when a stimulus intensity higher than the threshold for A fibers is used. Similar results were reported by Nilsson et al [17] and Nilsson and Schouenborg [18] who used a needle-like electrode. However, this indicates that the stimulus inevitably activates A fibers at the intensity necessary to activate C fibers.…”
Section: Introductionsupporting
confidence: 89%
“…The inhibition of itch by painful stimuli has been experimentally demonstrated by use of various painful thermal, mechanical, and chemical stimuli (S8). Painful electrical stimulation reduced histamine-induced itch for hours in an area spanning 10 centimeters beyond the site of stimulus, suggesting a central mode of action (48). Recent results suggest that noxious heat stimuli and scratching produce a stronger itch inhibition than do noxious cold stimuli (49).…”
Section: Itch Is Modulated By Painful and Nonpainful Stimuli: Role Ofmentioning
confidence: 99%
“…It requires ongoing activity in primary afferents and is most probably elicited by low-threshold mechanoreceptors (A-b fibers) (S12, S13). Moreover, even normally painful stimuli can be misinterpreted as itch in a chronic itch condition when applied directly to pruritic skin lesions (48,56).…”
Section: Chronic Skin Inflammation May Cause Central Itch Sensitizationmentioning
confidence: 99%